PROFIL PERIKANAN PANCING TONDA DEMERSAL DI PERAIRAN SELAT SAPE, KABUPATEN BIMA NUSA TENGGARA BARAT: Tonda Demersal Fisheries Fishing Profile in Sape Selat Waters, Bima Nusa Tenggara Barat District - Rabani, Din; Asrial, Evron; Rahmawati, Aryani; Tarmizi, Azhari (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2023)
The potential of fisheries resources in the Indonesian sea consists of four fishery resources, namely: large pelagic (451,830 tons per year) and small pelagic (2,423,000 tons per year), demersal fisheries resources (3,163,630 tons per year), shrimp (100,720 tons per year) per tofu) and reef fish (80,082 tons per year). This study aims to determine the catch using demersal trolling in the Sape Strait and to determine the biological status of fish caught by using a troll demersa fishing rod To determine the biological status of fish caught using demersal trolling rods. This research will be carried out in the waters of the Sape Strait of West Nusa Tenggara. Data collection methods used in this study are descriptive, quantitative and qualitative methods. These methods describe in detail all the activities carried out during the research activities, so that they are able to answer the problems or goals that have been set. The results of this study were processed using Fisheries Biology Analysis such as length and weight relationship pattern analysis, growth pattern analysis of the condition of the feasibility of the fishing gear analysis of fishing gear productivity effectiveness of fishing gear environmental friendliness analysis of the gear sensitivity of the fishing gear business feasibility analysis